DEVELOPMENT AND APPLICATION OF A DECISION MODEL FOR THE INTEGRATED PRODUCTION AND MATERIAL PLANNING OF COLOR FILTER MANUFACTURING INDUSTRY: AN EMPIRICAL STUDY - Leu, Jun-Der; Wen, Ta-Chun; Chang, Kuei-Hu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
Color Filters (CF) is a critical module of TFT-LCD industry whose products are widely applied to the customer electronics products. Since the color filters manufacturing stays in the 1-tier enterprise of the supply network of the TFT-LCD industry, its logistics planning is quite complex. This paper develops a LP-based planning method to support the logistics of a color filter manufacturing company. This developed planning model focuses on the mid-term planning, considering the issues in terms of production and material requirement planning in an integrated way. For application, this developed method is implemented by the optimization software LINGO and then integrated to the database system as decision support. To test the quality of this method, 52 weeks of real factory data are studied, and the validation result shows a variation less than 10%.